IMPLEMENTATION OF ISLAMIC SPIRITUAL EDUCATION INTELLIGENCE (STUDY OF THE QUR'AN SURAT AL-MUZAMMIL 1-8) - Ambyah; Muchothob Hamzah; Ahmad Zuhdi (Alphateach (Jurnal Profesi Kependidikan dan Keguruan), 2025)
This article aims to: 1) Examine the content of Surah Al-Muzzammil (verses 1–8) of the Qur'an. 2) Understand the concept of spiritual intelligence within Islamic education as found in Surah Al-Muzzammil (verses 1–8). 3) Determine how to implement the spiritual intelligence found in Surah Al-Muzzammil (verses 1–8) within Islamic education. This study is descriptive in nature and was conducted through a literature review. It is classified as library research, utilizing both primary and secondary data sources. Primary sources include Tafsir Ibn Kathir by Ibn Kathir, Tafsir Al-Azhar by Prof. Dr. Hamka, Tafsir Al-Misbah by Prof. Dr. M. Quraish Shihab, and the Ministry of Religious Affairs' (Kemenag) Tafsir (2019). Secondary sources consist of books, articles, scholarly journals, and other research findings related to spiritual intelligence. Data collection was carried out through documentation specifically, by studying and interpreting the selected Qur'anic verses. The data analysis techniques employed were content analysis and discourse analysis. The findings of this study indicate that the implementation of spiritual intelligence comprises four aspects: 1) The social aspect; indicators of this aspect include showing affection toward parents, one's spouse, and children; assisting those in need; demonstrating trustworthiness; possessing the courage to speak the truth; practicing honesty; and avoiding behaviors that create distance between oneself and others. 2) The spiritual/inner-self aspect; Indicators of the psychological aspect include honesty with oneself; a heart free from envy, malice, and hatred; acceptance of one's true self; the ability to overcome depression and anxiety; avoidance of things that harm the soul; steadfast adherence to Sharia principles; emotional balance; a broad-minded nature; spontaneity; acceptance of life; the ability to master and control oneself; and self-confidence. 3) Spiritual aspect; indicators of the spiritual aspect include the ability to distinguish between good and bad behavior, as well as the ability to socialize and interact with others. 4) Biological aspect: A mentally healthy person is characterized by the ability to resolve or overcome any inner turmoil arising from the complexities of life.